2012
DOI: 10.1590/s1806-37132012000200006
|View full text |Cite
|
Sign up to set email alerts
|

É possível diferenciar derrames pleurais linfocíticos secundários a tuberculose ou linfoma através de variáveis clínicas e laboratoriais?

Abstract: Objective: To describe clinical and laboratory characteristics in patients with tuberculosis-related or lymphomarelated lymphocytic pleural effusions, in order to identify the variables that might contribute to differentiating between these diseases. Methods: This was a retrospective study involving 159 adult HIV-negative patients with tuberculosis-related or lymphoma-related lymphocytic effusions (130 and 29 patients, respectively), treated between October of 2008 and March of 2010 at the Pleural Diseases Out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…A patient with an effusion of malignant aetiology had only a 3% (6/172) chance of having a high pfADA and 0% (0/172) chance of the effusion also being lymphocyte predominant. The ability of pfADA to act as a ‘rule in’ test for mTB was greatly improved by consideration of the predominant cell type, increasing the specificity from 91% in all cause effusions to 99% in lymphocytic effusions.Six cases (2 NSCLC and 4 MPM) of malignant cause effusions had a high pfADA, although five appeared to have a co-existent pleural infection In other studies, high pfADA values have been reported in lymphoma[ 11 , 19 , 20 ], although all lymphoma cases in our cohort had pfADA values of less than 35 IU/L. Differentiating between mTB and lymphoma can be challenging, and additional tests such as lymphocyte subset analysis may help to distinguish one from the other[ 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…A patient with an effusion of malignant aetiology had only a 3% (6/172) chance of having a high pfADA and 0% (0/172) chance of the effusion also being lymphocyte predominant. The ability of pfADA to act as a ‘rule in’ test for mTB was greatly improved by consideration of the predominant cell type, increasing the specificity from 91% in all cause effusions to 99% in lymphocytic effusions.Six cases (2 NSCLC and 4 MPM) of malignant cause effusions had a high pfADA, although five appeared to have a co-existent pleural infection In other studies, high pfADA values have been reported in lymphoma[ 11 , 19 , 20 ], although all lymphoma cases in our cohort had pfADA values of less than 35 IU/L. Differentiating between mTB and lymphoma can be challenging, and additional tests such as lymphocyte subset analysis may help to distinguish one from the other[ 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…The relative abundance of T lymphocytes, which orchestrate the inflammatory response to tuberculosis, induces an elevation in ADA levels, particularly noticeable in cases of TBP. Nonetheless, pleural lymphocytic infiltration secondary to lymphoma also leads to an increase in pleural effusion ADA levels, with 25–56% of lymphomatous pleural effusions demonstrating ADA levels above the standard TB cutoff [ 9 , 18 , 19 ]. ADA levels exceeding 40 IU/L are not exclusive to lymphoma, as similar elevations can also be observed in pleural effusion secondary to leukemia or multiple myeloma.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 10 cases reviewed, 8 had lymphocyte-predominant (Ly+Aty-Ly >70%) exudative effusion, and 9 had a high level of ADA (>40 U/L). Although one-third of the PEL-LL cases had elevated serum LDH levels (>500 U/L), tuberculous pleural effusion was also often elevated to approximately 500 U/L ( 39 ). While sIL2R levels >2,000 U/L are an indicator of malignant lymphoma ( 40 ), only 2 of the 9 cases of PEL-LL had such high levels of sIL2R.…”
Section: Discussionmentioning
confidence: 99%